Investigating the Institutional Quality Integration with Islamic Banking ‎Development in Promoting Entrepreneurship - SOHAIL, HADIA; ARSHAD, NOMAN (International Journal of Islamic Economics and Governance, 2022)
Empirically, conventional finance has proven insufficient while providing the ‎required finance for startups and entrepreneurs. While handling the risks, ‎entrepreneurs tend to avoid the high-cost nature of the debt, which limits their ‎true potential leading to sub-optimal resource utilization. For this, Islamic finance ‎provides a participative and equitable alternative for new ventures with proven ‎merits, but a lack of regulation hinders its penetration among entrepreneurial ‎aspirants. This study investigates how Islamic finance assists entrepreneurial ‎decisions and the role of institutional quality in aligning Islamic law with ‎commercial law requirements. This study selected the unbalanced panel data of 37 ‎countries between 2011 and 2020 and used panel quantile regression to estimate ‎the quadratic Islamic financial development effects and the moderation of ‎institutional quality. The results showed that generally, Islamic financial ‎development has a U-shaped relation with entrepreneurship, but with the ‎improvement in institutions, the U shape is flipped to inverted-U shape. This study ‎points toward the potential of Islamic financing when coupled with better ‎regulations for the economies which are developing the nascent Islamic financing ‎system.